The Impact Analysis of Privatization and Shariah Screening on Financial Performance and Shares Return of State Owned Enterprises as the member of Jakarta Islamic Index - Lubis, Mursid; Basri, Yuzwar Z.; Mariyanti, Tatik (International Journal of Islamic Banking and Finance Research, 2017)
Privatization is one of the government’s programs in restructuring State-Owned Enterprises (SOEs). Other than restructuring SOE, privatization is also source of state budget funds (APBN). By privatizing SOE, government expected healthy corporation that will contribute larger tax payments, dividend payments, and additional paid-in capital. So it is expected that SOEs are always in a healthy condition, high competitive and produce goods quality products and services.In order to invite Islamic foreign investors. Now also available public listed SOEs that is according to Islamic sharia. SOE sharia shares are expected to be an example of implementing business in accordance to sharia, will benefit better financial performance and better share price. Eight SOEs who are members of the Jakarta Islamic Index, those are WSKT, WIKA, PTPP, SMGR, TLKM, PTBA, ANTM and PGAS, will be evaluated in this research regarding their financial performance and stock performance during the period 2000 to 2016.This research is included in descriptive research method that is ex post facto. The researcher evaluated the company’s financial performance and stock performance during the 17-year period, from 2000 to 2016, financial performance measured is profitability performance (NPM, ROA and ROE), solvency (Total Asset Turnover) activity (Debt to Equity Ratio). The measurement of stock performance those are EPS. PER and PBV. Data analysis used in this research is descriptive analysis, trend analysis and Test t test.Based on the results of the study, the variable condition before the regression, NPM, ROA, ROE, DER, DR, DI, S / TA, EPS, PER and PBV variables have scattered residues normally. However, when tested for heteroscedasticity using scatter diagrams these variables such are NPM, ROA, ROE and PER free from heteroscedasticity. But variables such as DER, DR, DI, S/TA, EPS and PBV variables tend to contain heteroscedasticity. NPM variable data, tends to increase every year, as well as ROA, ROE. However, DER, DR, DI, S / TA, EPS, PER and PBV variables tend to be stable from year to year.Through a simultaneous equation method that reflects the existence of circular causation, it gives an idea of all variables being independent and dependent. Variable net profit margin on each SOE member JII, influenced significantly by the variable ROE, DER, DR, PER, PBV. The variable return on asset is influenced by ROE and DER variables significantly. The return on equity variable is significantly influenced by NPM, ROA, DER, PER and PBV variables. Debt To Equity Ratio (DER) variables are influenced significantly variables of NPM, ROA, ROE, DER, PER and PBV. Days Receivable (DR) variables influenced by NPM variables significantly.Days Inventory variables are not affected by any variable. Variable of Asset Turn Over (S / TA) is influenced by one variable only that is EPS. Variable Earning per Share (EPS) influenced significantly by variable DER and S / TA. Price Earning Ratio (PER) variables are significantly influenced by NPM, ROE, DER, and PBV. Price to Book Value (PBV) variables are significantly influenced by NPM, ROE, DER and PER variables.